Genome-wide association mapping for seed protein content in finger millet (Eleusine coracana) global collection through genotyping by sequencing. (January 2020) - Tiwari, Apoorv; Sharma, Divya; Sood, Salej; Jaiswal, Jai Prakash; Pachauri, Satya Pratap; Ramteke, Pramod Wasudeo; Kumar, Anil
Abstract: Finger millet is a nutritious cereal and marker assisted breeding is essential for the identification of genes/alleles governing quality traits in finger millet. This study used an integrated breeding strategy supported by genomics, where selective genotyping of 113 diverse finger millet genotypes was carried out for understanding the complex genetic architecture of SPC (seed protein content) and related traits like DM (days to maturity) and GY (grain yield) in two geographically different locations in India i.e. Almora (E1) and Pantnagar (E2). Significant differences among genotypes were observed for SPC, DM and GY in both the locations. A set of 2977 genome-wide SNPs identified through genotyping by sequencing were used for MTA analysis. GLM resulted in 7, 10 and 9, while MLM found 4, 9 and 7 MTA's for SPC, DM and GY, respectively across the locations using TASSEL pipeline. Among GLM and MLM 4, 7 and 6 MTA's were found common for SPC, DM and GY, respectively. Another pipeline, GAPIT identified 12 MTA's each for SPC, DM and 11 MTA's for GY across the locations. NCBI blast of common SNP markers for all three traits resulted in 5, 3 and 5 most effective genome regions associated with SPC, DM and GY. Among them, the SNP responsible for gene encoding aspartyl protease exhibited strong SPC association and was found to be the most promising candidate for protein content variation in finger millet. For GY and DM, ATP synthase gene which catalyses the addition of a phosphate to ADP, capturing energy from the proton gradient as ATP was found prominent gene. Expression results for five genes associated with SPC showed higher transcript accumulation in high protein containing genotype in comparison to low protein containing genotype. Graphical abstract: Image 1 Highlights: Significant genotypic differences were observed for SPC, DM and GY in E1 & E2. Five SNPs were found to be significantly associated with SPC, GY and three with DM trait in finger millet. Aspartyl protease was found as most promising candidate gene governing SPC content in finger millet grains.